A Note on the Minimal Period Problem for Second Order Hamiltonian Systems - Huafeng Xiao (Abstract and Applied Analysis, 2014)
We study periodic solutions of second order Hamiltonian systems with even potential. By making use of generalized Nehari manifold, some sufficient conditions are obtained to guarantee the multiplicity and minimality of periodic solutions for second order Hamiltonian systems. Our results generalize the outcome in the literature.